2009
DOI: 10.1073/pnas.0908201106
|View full text |Cite
|
Sign up to set email alerts
|

C-end rule peptides mediate neuropilin-1-dependent cell, vascular, and tissue penetration

Abstract: Screening of phage libraries expressing random peptides for binding to prostate cancer cells primarily yielded peptides that had a Cterminal arginine (or rarely lysine) residue, usually in a consensus context R/KXXR/K. Phage expressing these sequences and synthetic nanoparticles coated with them bound to and were internalized into cells. The C-terminal arginine (or lysine) was essential to the activity; adding another amino acid, or even blocking the free carboxyl group of this arginine residue by amidation, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
807
5
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 698 publications
(855 citation statements)
references
References 36 publications
15
807
5
3
Order By: Relevance
“…Previous studies have shown that peptides with a C-terminal (R/K)XX(R/K) sequence exhibit significantly higher affinity for NRP-1-expressing cells than peptides with a C-terminal arginine alone (XXXR) (29). We found that the MiPS system enables more efficient enrichment of phage displaying this higher-affinity motif (Fig.…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…Previous studies have shown that peptides with a C-terminal (R/K)XX(R/K) sequence exhibit significantly higher affinity for NRP-1-expressing cells than peptides with a C-terminal arginine alone (XXXR) (29). We found that the MiPS system enables more efficient enrichment of phage displaying this higher-affinity motif (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…We then seeded the chamber with ∼10 4 PPC-1 human prostate carcinoma cells in 2 mL of culture medium. PPC-1 cells were selected as a model because they express high levels of NRP-1, a well characterized receptor that binds and internalizes peptides with C-terminal arginine residues, typically within a consensus context of R/KXXR/K (the C-end Rule or CendR motif) (29)(30)(31). As a negative control, we used phage expressing hepta-glycine (G7), which exhibits negligible binding to PPC-1 cells (28).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…18 All NRP1-binding proteins and peptides are found to possess a C-terminal arginine. 17 , 19 - 21 The authors further showed that NRP1 has a C-terminal arginine-binding pocket in the b1 domain. Mutating VEGF's C-terminal exon 8a-encoded arginine (R164) resulted in up to 97% loss in retention of mouse VEGF-A164a by NRP1, thus this residue plays a critical role in VEGF-A/NRP1 interactions (Fig.…”
Section: Evidence That the Exon 8a Domain Which Vegf-a121a Has Is Rmentioning
confidence: 98%